2022
DOI: 10.1111/ctr.14609
|View full text |Cite
|
Sign up to set email alerts
|

Changing opportunities for liver transplant for patients with hepatocellular carcinoma

Abstract: Introduction Aim was to study the early impact of acuity circle‐based allocation implementation system on liver transplantation for hepatocellular carcinoma (HCC) patients. Methods We assessed characteristics of HCC and non‐HCC deceased donor orthotopic liver transplants (OLT) in the year before (2/2019–2/2020) and after (3/2020–2/2021) introduction of the acuity circle policy using the Organ Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing (UNOS) database. Results Total OLTs red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A recent study looked at changes for patients with HCC 1 year before and after acuity circles was enacted and found that 6/11 UNOS regions had decreases in the absolute number of HCC transplants, with Regions 2 and 4 having statistically significant decreases in transplants for patients with HCC. [ 9 ] Our study provides novel data on the geographic variability in the impact of the policy changes in transplantation for patients with HCC. We provide a longitudinal view of changes for 16 years and four major eras.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study looked at changes for patients with HCC 1 year before and after acuity circles was enacted and found that 6/11 UNOS regions had decreases in the absolute number of HCC transplants, with Regions 2 and 4 having statistically significant decreases in transplants for patients with HCC. [ 9 ] Our study provides novel data on the geographic variability in the impact of the policy changes in transplantation for patients with HCC. We provide a longitudinal view of changes for 16 years and four major eras.…”
Section: Discussionmentioning
confidence: 99%
“…[60] These differences by region stem from geographic variation in the MELD score needed to receive LT. [61] Although AC was predicted to decrease this geographic variation in MMaT, early studies suggest that AC has not accomplished this goal. [62,63] As we currently stand, for HCC patients within Milan Criteria with the same MELD exception points, there continues to be geographic variation in LT rates as a result of patients being listed in areas with very different MMaT.…”
Section: Geographic Disparities By Region and Neighborhood Hcc And Po...mentioning
confidence: 99%
“…From the perspective of transplant centers, another growing concern surrounding the new AC policy is increased cost and allocation of resources, with some studies finding an increase in cost and distance traveled between transplant and donor hospitals. [5][6][7][8][9] Knowledge about the satisfaction levels and perceptions among transplant surgery staff in the United States is lacking. Further delineation of geographic disparities in transplant metrics and the perceived impact of the AC among transplant surgeons is needed to better understand the strengths of the AC policy and to identify areas of improvement for future policy decision-making.…”
Section: Introductionmentioning
confidence: 99%